Análise de questões de trigonometria propostas aos alunos do Ensino Fundamental pelo SARESP - Pastor, Ederson Sales (2020)
This dissertation aims to investigate which sets of tasks are present in the questions related to trigonometry in the right triangle, proposed by SARESP in the years 2010 to 2018, and which sets of techniques, technologies and theories can be mobilized by 9th grade students of elementary school in solving these mathematical issues. We rely on the Anthropological Theory of Didactics (TAD) for the development of the praxeological analysis of the questions proposed by SARESP selected for this work. After the development of the praxeological analysis of the questions, we sought to apply them to students of the 9th grade of elementary school in two schools of the State Education Network of the State of São Paulo in order to observe and identify the mobilizations, by the students, of the techniques, technologies and theories in the resolution of the proposed questions and for that we resort to qualitative research methodology. After the development of the research, we concluded that the questions proposed by SARESP selected for this investigation start from the same type of task and for the resolution, the same mobilizations of techniques are necessary, which in turn are justified by the same theoretical-technological discourse. We also identified that a considerable group of students participating in our investigation correctly presented the mobilizations of the techniques related to trigonometry in the right triangle, but presented errors when performing the arithmetic operations